How should domestic auditors live on (novels of legislative regulation of audit in Ukraine) - О. Yu. Redko (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
The article is written in form of the author’s review of the Law of Ukraine “Audit of Financial Reporting and Auditing” from 21.12.2017, adopted on January 1, 2018, which will be enforced on October 1, 2018. Like any other domestic legal act, this Law has its strong and weak sides (signified in the text as “plus” and “minus”) for the occupation that is 25 years old in Ukraine.Assessments of strong and weak sides of the new Law are made with two considerations born in mind. The first one that Ukrainian auditors will have to live very soon by the rules adapted as maximally as possible to European ones; the second one is that 25 years of audit practice in Ukraine have formed certain professional image and stereotypes of audit services, which will supposedly create a discomfort in the auditors’ work by the new Law.The main stereotypes are intentions to monopolize the market of auditor services and fix its prices; treatment of audit personnel by managers of audit firms as ones whose intellect and competencies are “appropriated” by a firm; conflicts of interests and personal conflicts with leaders of the audit community. It should be remembered that domestic auditors have not been prone to obey the administrative control to be enforced by the new Law. The review of the Law results in 28 weak sides and 36 strong sides revealed and explicated in table form. It allows for making the following general conclusions: the auditor practice will be more bureaucratized than before; the market performance will depend on the breaking of audit entities into the two equal groups: professional audit firms and the rest, with the expected perpetual rotation in the latter group; the quality of audit services will not change unless quality criteria and rules of audit are clearly defined in the subsidiary legislation; a new professional organization of auditors, the Auditor Chamber of Ukraine, need to be staffed with rational practitioners from the Ukrainian audit rather than politicians or public officers.